The Role of Students' Critical Thinking Ability in Learning Mathematics with Problem Solving - Harahap, Vina Fauziah (Lembaga Riset Mutiara Akbar, 2023)
The purpose of this article is to discuss how learning mathematics through problem solving can develop students' critical thinking abilities. To achieve this goal, the method used is to describe how learning mathematics through problem solving can develop students' critical thinking skills based on research on supporting references. In the era of globalization, someone can obtain information in various ways, places and times. So that the information a person obtains is useful and does not have a negative impact, a